1989
DOI: 10.1002/ajpa.1330780105
|View full text |Cite
|
Sign up to set email alerts
|

Yugoslav Mesolithic dental reduction

Abstract: Yugoslav Mesolithic dentition exhibits maximum mesiodistal reduction compared with contemporary European and North African groups. This reduction is not explained entirely by attrition, and may be seen as a continuation of the European Upper Paleolithic trend. Buccolingual dimension does not reduce as much. In fact, this dimension in premolars and molars is larger than in other groups. This observation also occurs in Natufians, who were grain collectors, hunters, and gatherers. The Yugoslav Mesolithic group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(6 citation statements)
references
References 81 publications
0
5
1
Order By: Relevance
“…Although previous authors have proposed that agriculturalists would show reduced tooth size (Hinton et al, 1980;Larsen, 1995;Y'Edynak, 1989), this idea is not clearly reflected in our results, as Agta and San, who are typical hunting and gathering groups, have smaller teeth than Navajo, who have an agro-pastoral subsistence pattern. This inconsistency suggests that genetic factors determine dental size, rather than external or environmental influences (Dempsey et al, 1999;Garn et al, 1977).…”
Section: Intergroup Variationcontrasting
confidence: 90%
See 1 more Smart Citation
“…Although previous authors have proposed that agriculturalists would show reduced tooth size (Hinton et al, 1980;Larsen, 1995;Y'Edynak, 1989), this idea is not clearly reflected in our results, as Agta and San, who are typical hunting and gathering groups, have smaller teeth than Navajo, who have an agro-pastoral subsistence pattern. This inconsistency suggests that genetic factors determine dental size, rather than external or environmental influences (Dempsey et al, 1999;Garn et al, 1977).…”
Section: Intergroup Variationcontrasting
confidence: 90%
“…Dental wear reduction is an evolutionary trend that is usually associated with the implementation of new technologies and methods of food processing and dietary changes (Hinton et al, 1980;Larsen, 1995;Y'Edynak, 1989). These studies revealed a relationship between this trend and the decline of the nutritional status of foods consumed in agricultural populations, which reduced maternal health status and resulted in smaller permanent teeth in children (Larsen, 1995).…”
Section: Hunter-gatherers Vs Agriculturalistsmentioning
confidence: 99%
“…Nevertheless, it seems that the distribution of this bacterial species was related neither to the food mode, nor to the conditions of life [21]; this observation is opposed to that of a Mesolithic bone collection from Yugoslavia that showed sex differences of calculus and dental wear distribution revealing different food modes [22]. Dental calculus was found particularly frequent in a population of the Bronze Age (2000 years B.C.)…”
Section: Precedent Studies On Dental Calculus From Skeletal Remainsmentioning
confidence: 99%
“…During the middle ages, some physicians understood the etiology of gum disease. For example, in the Ottoman Empire, the physician Şerafeddin Sabuncuoğlu recognized calculus deposits as a risk factor for periodontal disease and the need to remove them via scaling (Yilmaz et al,1994). However, according to Yilmaz et al (1994), even though the benefits of such procedures were understood during the middle ages, they were rarely performed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Ottoman Empire, the physician Şerafeddin Sabuncuoğlu recognized calculus deposits as a risk factor for periodontal disease and the need to remove them via scaling (Yilmaz et al,1994). However, according to Yilmaz et al (1994), even though the benefits of such procedures were understood during the middle ages, they were rarely performed. Anderson (2004) describes various dental care practices that were recommended in medieval literature.…”
Section: Discussionmentioning
confidence: 99%